Preparing for future pandemics while responding to the current ones in the midst of a planetary climate crisis: Can we face this triple global health challenge? - Dulce Ferraz; Draurio Barreira (Taylor & Francis Group, 2024)
ABSTRACTGlobal health faces the triple challenge of preparing for future pandemics while responding to current ones in the midst of a climate crisis. In this commentary, we discuss the heightened focus on pandemic preparedness after the COVID-19 pandemic and the risks that this may pose to addressing the elimination of AIDS, tuberculosis, hepatitis and malaria, established in the Sustainable Development Goals as target 3.3. Considering their interconnections with the climate crisis and advocating for global health justice, we identify impasses that such a dispute over priorities can imply, and comment on four fronts of actions that could contribute convergently to both agendas as well as to facing the consequences of climate change to health: strengthening health systems, global commitment to equitable access to strategic medicines, addressing social inequalities and joining efforts for health and climate justice We conclude that addressing these fronts safeguards the health rights of the most vulnerable to existing epidemics while enhancing readiness for future pandemics. Moreover, solutions must transcend technocratic approaches, necessitating the confrontation of inequalities perpetuated by systems of power and privilege fueling both health and climate crises. Ultimately, health justice should guide responses to this intricate triple global health challenge.